1997
DOI: 10.1103/physrevlett.79.2771
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Scattering of Halo Nuclei

Abstract: We show that under certain conditions a simple relationship exists between the elastic scattering of a composite halo nucleus and of its core from a stable target. The coupling of the elastic and projectile excitation channels is crucial to the analysis, which is particularly useful when the ratio of the halo to the core mass is small. In the case of 11 Be elastic scattering the cross section relationship is quite well satisfied. For both 11 Be and 19 C our analysis reveals a significant sensitivity of elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(142 citation statements)
references
References 12 publications
11
131
0
Order By: Relevance
“…For the reaction at 229.8 MeV we conclude that the effect of coupling to the continuum is a reduction of the cross section for angles beyond 5 • . This effect has also been observed in the scattering of 11 Be+ 12 C at E 49 MeV per nucleon [37], and is probably present in other reactions induced by weakly bound projectiles at energies of a few tens of MeV per nucleon. That the no-continuum coupling calculation reproduces the data reasonably well at the larger angles is probably fortuitous, and cannot be attributed to the adequacy of this approximation.…”
Section: -4mentioning
confidence: 71%
See 1 more Smart Citation
“…For the reaction at 229.8 MeV we conclude that the effect of coupling to the continuum is a reduction of the cross section for angles beyond 5 • . This effect has also been observed in the scattering of 11 Be+ 12 C at E 49 MeV per nucleon [37], and is probably present in other reactions induced by weakly bound projectiles at energies of a few tens of MeV per nucleon. That the no-continuum coupling calculation reproduces the data reasonably well at the larger angles is probably fortuitous, and cannot be attributed to the adequacy of this approximation.…”
Section: -4mentioning
confidence: 71%
“…The theoretical understanding of reactions involving a three-body projectile, such as 6 He, is a complicated task because it requires the solution of a four-body scattering problem. At high energies, a variety of approximations have been used such as semiclassical approximations [34][35][36], frozen halo or adiabatic approximations [37,38], multiple scattering expansions [39][40][41], fourbody DWBA [42,43], among others. However, at energies of a few MeV per nucleon, some of these approximations are not justified.…”
Section: Introductionmentioning
confidence: 99%
“…There are in the literature a number of papers discussing the breakup potential for a 11 Li projectile, among others [22,15,18,19]. 11 Be breakup from the 2s has been discussed in [20,21]. However the potential due to breakup of the 1p 1/2 bound excited state has never been discussed before.…”
Section: Resultsmentioning
confidence: 99%
“…The adiabatic model, i.e., the neglect of the breakup Q-value, is generally used at higher energies, as done in [154], and [155]. In [154] the Glauber approximation while in [155] the usual adiabatic Schrdinger model are used for the radial wave function.…”
Section: Coupled Channelsmentioning
confidence: 99%
“…In [154] the Glauber approximation while in [155] the usual adiabatic Schrdinger model are used for the radial wave function. The result of the analysis of the total reaction cross section in [154] of 11 Li,11 Be, and 8 B and a 12 C target, demonstrated that the breakup channel coupling necessarily increases the reaction cross section and accordingly requires a larger rms radius of the halo nucleus, as seemed to be required by the data on the interaction cross section (the total reaction cross section without the projectile inelastic or breakup contributions) at the time, which were analyzed using the optical, eikonal, approximation [156,157].…”
Section: Coupled Channelsmentioning
confidence: 99%